Crossmodal illusions in neurorehabilitation - Bolognini, Nadia; Russo, Cristina; Vallar, Giuseppe (Frontiers in Behavioral Neuroscience, 2015)
In everyday life, many diverse bits of information, simultaneously derived from the different sensory channels, converge into discrete brain areas, and are ultimately synthetized into unified percepts. Such a multisensory integration can dramatically alter the phenomenal experience of both environmental events and our own body. Crossmodal illusions are one intriguing product of multisensory integration. This review describes and discusses the main clinical applications of the most known crossmodal illusions in rehabilitation settings. We consider evidence highlighting the contribution of crossmodal illusions to restore, at least in part, defective mechanisms underlying a number of disorders of body representation related to pain, sensory, and motor impairments in neuropsychological and neurological diseases, and their use for improving neuroprosthetics. This line of research is enriching our understanding of the relationships between multisensory functions and the pathophysiological mechanisms at the basis of a number of brain disorders. The review illustrates the potential of crossmodal illusions for restoring disarranged spatial and body representations, and, in turn, different pathological symptoms.